Investigating the Adjuvanticity of K. pneumoniae Capsular Polysaccharide with Formalin-Killed S. aureus Against Live S. aureus Infection in Mice - Al-Rhman , Rand M. Abd; Al-Aubydi , Mouruj A. (Iraqi Journal of Science, 2022)
Klebsiella pneumoniae capsular polysaccharide (CPS) antigen was evaluated for their capability to increase immune responses. And, CPS neutralizing antibodies were approved as the main response to vaccination in many disease. Therefore, killed Stapthylococcus aureus bacteria was employed to evaluate K. pneumoniae CPS adjuvanticity. The mice groups were immunized (orally, intra-peritoneally and by swab skin)with a dose of (25μl of formalin killed S. aureus (1.5 x 108) with a CPS at dose 175μl/kg at a conc.50 μg/ml) vaccination occurred in first day then recurrent vaccination as booster dose beyond seven days. After first 7 days, the results revealed elevation of IL2,4,10,12 and IgG levels occurred mainly in oral and swab skin groups, and the obvious elevation seen in all treated groups especially oral and swab skin groups after booster dose compared with the negative control. On the other hand these results were in concordance with the challenge test which elucidated the treated groups were survived compared with the negative control one.Thus, the formalin killed- CPS vaccine induce immune response against live S. aureus compared to CPS alone as positive control and Freund’s incomplete adjuvant, therefore this suggest that CPS have adjuvant effect on immune responses against S. aureus bacteria which is important in clinical treatment of S. aureus disease.